Active surveillance study of adverse events following immunisation of children in the Czech Republic - Danova, Jana; Kocourkova, Aneta; Celko, Alexander M (BMC public health, 2017)
BACKGROUND: Despite the undisputed public health benefits of routine vaccination, adverse events following immunisation (AEFI) remain a concern. As most adverse events are mild, they may be under-reported; this may underlie the wide range of AEFI rates reported in the literature. We investigated the rates of AEFI related to routine vaccination of children 0-10 years old in the Czech Republic. METHODS: The study reviewed patients' records in a sample of 49 paediatric GP practices covering all 12 administrative regions of the Czech Republic between 2011 and 2013. Adverse events following routine immunisation of children aged 0-10 years were identified and recorded. RESULTS: The overall rate of AEFI was 209/100,000 doses; this was 6 times higher than the rate reported to the Czech State Institute for Drug Control (34/100,000 doses). Over two fifths (44%) of all AEFI occurred after the booster dose of the combined diphteria, tetanus and pertussis vaccine in 5-year old children. The vast majority of AEFI were non-serious local events (e.g. redness) and fever. Most AEFI occurred the second day after the immunisation, lasted 4 days on average, and were treated by cold therapy, antipyretics and analgesics. CONCLUSIONS: The rate of AEFI identified in this study was considerably higher than the officially reported rate. Although the vast majority of AEFI were non-serious, health care providers and the public should be educated and encouraged to report AEFI to address the issue of underreporting, to increase the safety profile of vaccines, and to improve public confidence in immunisation programmes.
Keywords: Female; Infant; dítě; předškolní dítě; novorozenec; Age Factors; ženské pohlaví; vakcinace; Adolescent; věkové faktory; lidé; Infant, Newborn; surveillance populace; Adverse Drug Reaction Reporting Systems; Vaccination; Male; kojenec; Czech Republic; Child, Preschool; Population Surveillance; Česká republika; Child; mužské pohlaví; mladiství; systémy pro sběr zpráv o nežádoucích účincích léků; Humans